The Invasive Tradescantia zebrina Affects Litter Decomposition, but It Does Not Change the Lignocellulolytic Fungal Community in the Atlantic Forest, Brazil - Wagner Antonio Chiba de Castro; Giselle Cristina de Oliveira Vaz; Dalva Maria da Silva Matos; Alvaro Herrera Vale; Any Caroline Pantaleão Bueno; Luiz Fernando Grandi Fagundes; Letícia da Costa; Rafaella Costa Bonugli Santos (Plants, 2023)
Invasive plants affect ecosystems across various scales. In particular, they affect the quality and quantity of litter, which influences the composition of decomposing (lignocellulolytic) fungal communities. However, the relationship among the quality of invasive litter, lignocellulolytic cultivated fungal community composition, and litter decomposition rates under invasive conditions is still unknown. We evaluated whether the invasive herbaceous Tradescantia zebrina affects the litter decomposition in the Atlantic Forest and the lignocellulolytic cultivated fungal community composition. We placed litter bags with litter from the invader and native plants in invaded and non-invaded areas, as well as under controlled conditions. We evaluated the lignocellulolytic fungal communities by culture method and molecular identification. Litter from T. zebrina decomposed faster than litter from native species. However, the invasion of T. zebrina did not alter decomposition rates of either litter type. Although the lignocellulolytic fungal community composition changed over decomposition time, neither the invasion of T. zebrina nor litter type influenced lignocellulolytic fungal communities. We believe that the high plant richness in the Atlantic Forest enables a highly diversified and stable decomposing biota formed in conditions of high plant diversity. This diversified fungal community is capable of interacting with different litter types under different environmental conditions.